A Stochastic Income Model Using Optimal Inventory Rules - Orr, Daniel (Review of Economic Studies, 1963)
Journal Article A Stochastic Income Model Using Optimal Inventory Rules Get access Daniel Orr Daniel Orr Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 2, June 1963, Pages 84–92, https://doi.org/10.2307/2295805 Published: 01 June 1963